Effects of Climate Change on Weeds and Invasive Alien Plants in Sri Lankan Agro-Ecosystems: Policy and Management Implications - Marambe, Buddhi; Wijesundara, Siril (Frontiers in Agronomy, 2021)
The progressive nature of climatic changes has worsen the problems caused by weeds and invasive alien species (IAS) in agro-ecosystems at global scale resulting from their changes in the range and population densities. A slow but steady increase in environmental temperature at a rate of 0.01 to 0.03 °C per year over the past six decades, increasing extreme events of rain fall, wetter wet seasons and drier dry seasons are some of the characteristic features of the changes in the climate observed in Sri Lanka over the years. Sri Lanka has formulated a National Weed Strategy (NWS) in 2017 and a National Policy, Strategy and Action Plan for invasive alien species in 2016. A National Invasive Species Specialist group (NISSG) has been set up by the Ministry of Environment. Further, pre-entry and post-entry risk assessment protocols have been developed incorporating climate change concerns, and periodic risk assessments being carried out to identify priority invasive alien species in Sri Lanka. Sri Lanka has identified the Weeds of National Significance (WONS) under difference priority crops. A study done in 2014 has clearly shown that weed control costs in agricultural lands in several district of Sri Lanka were high during the years that experienced El Niño Southern Oscillation (ENSO). Further, studies have clearly indicated that weeds and other pests often do better if there is disruption in the ecosystems. Several species of invasive alien plants such as Panicum trichocladum, a species listed as a potential invasive based on the risk assessment done in 2016, have shown an increase in their population densities and distribution in Sri Lanka during the last 2-3 years. However, weeds and IAS in agro-ecosystems have received insufficient recognition in climate change discussions in island ecosystems. This paper will focus on the scientific evidence and observations on the impact of climate change on agriculturally important weeds and invasive alien flora in agro-ecosystems in Sri Lanka, and the efforts made to manage their introduction and spread among vulnerable and fragile ecosystems across the diverse agro-ecological regions in the country.